Comparison of Methods of Assessment and Results of Traditional Osce with Electronic-Osce - Mehvr Ismail, Mashala Rehman, Khadija Irshad, Zarafshan Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The onset and rise of COVID-19 and its sudden progression to a worldwide pandemic lead medical and dental institutes to change their way of teaching and conducting assessments to distance learning as compared to the previously applied conventional approaches. Teaching and assessment during this era have changed vastly, earlier it was solely traditional/live Objective Structured Clinical Examination (OSCE) but due to the current circumstances electronic/online OSCE (E-OSCE) method was introduced. In Pakistan also, Pakistan Medical Council (PMC) and the College of Physicians and Surgeons of Pakistan (CPSP) conducted online exams so that the scheduled exams do not get delayed. Aim: The main objective of this paper is to measure the reliability of an E-OSCE and to compare it with the traditional OSCE. Methodology: This was a cross-sectional study which got conducted at the Rawal Institute of Health Sciences, Islamabad. Traditional OSCEs and E-OSCEs were conducted with 71 participants including final year students and house officers. Each OSCEs had 10 stations, including one interactive station in traditional OSCE. Students’ scores in both the OSCEs were collected and paired t-test was used to compare the mean scores at p<0.05. Results: Total number of house officers were 27 and final year students were 44. The scores of 71 participants were collected. The difference between mean scores of house officers’ traditional OSCE and E-OSCE was statistically significant (p=0.000). The difference between final year students traditional OSCE and E-OSCE was also statistically significant (p=0.020). Finally, the overall difference between traditional OSCE and E-OSCE was also statistically significant (p=0.000) Practical implication: The main objective of this study was to assess the reliability of an E-OSCE and to compare whether the electronic method of conducting OSCE is more reliable than the traditional method of conducting OSCE. Conclusion: Despite limitations and the biases, the results of E-OSCE proved to be better than traditional OSCE. Further research needs to be conducted on E-OSCE to control the factors causing biases and limitations. Keywords: Traditional OSCE, E-OSCE, COVID-19, methods of assessment, medical education, dental education, distance learning.